PENGARUH PENGGUNAAN MEDIA WAYANG TERHADAP KETERAMPILAN MENYIMAK CERITA SISWA KELAS V DI SD 1 PETIR PIYUNGAN BANTUL - Mila, Mila; Anafiah, Siti (Universitas Sarjanawiyata Tamansiswa, 2021)
This study descriptively to find the tendency of listening skill to the story class V SD 1Petir, Piyungan, Bantul by using puppet media and hand puppet media. Comparatively to describe the differences in the use of puppet and hand puppet for the sill of listening to stories class V SD 1 Petir, Piyungan, Bantul. This research is a type of experimental research. This research was conducted at SD 1Petir, Piyungan, Bantul with a population of all class V consisting of 38 students. The sample used was random sampling. Class VA as an experimental class and class VB as a control class. Data was collected using the test, observations, and documentation techniques. The data analysis technique used prerequisite t-test analysis, including the distribution, normalize test, and the variance homogeneity test. The hypothesis in this study is the use of puppet media influences the student's skill of listening to stories class V SD 1 Petir, Piyungan, Bantul. The results of the posttest t-test calculation of the experimental class and the control class obtained values p = 0,013 < 0,05, then it can be stated that the hypothesis is accepted, that there is a very significant effect using puppet media on the listening skills of class students V SD 1 Petir, Piyungan, Bantul. The average score of the control class was 73,72 which was classified as a high category, in contrast to the average score of experimental class 78,80 which was classified as very high with a difference of 05,08. Based on the score data above, it can be seen that the teacher must choose innovative learning media so that it can improve students learning abilities in the classroom, especially listening skills.